A different PET test: The relationship between pet ownership and peritonitis risk in the Peritoneal Dialysis Outcomes and Practice Patterns Study (PDOPPS). Issue 3 (May 2023) - Boudville, Neil; McCullough, Keith; Bieber, Brian; Pisoni, Ronald; Kanjanabuch, Talerngsak; Kawanishi, Hideki; Kim, Yong-Lim; Wilkie, Martin; Nitta, Kosaku; Piraino, Beth; Teitelbaum, Isaac; Perl, Jeffrey
Pet ownership is common around the world, with pet ownership increasing in many countries. Current guidelines are not supportive of pet ownership for peritoneal dialysis (PD) patients. We examined the association between ownership of cats and dogs and the incidence of peritonitis among PD patients participating in the prospective, observational Peritoneal Dialysis Outcomes and Practice Patterns Study. A total of 3655 PD patients from eight different countries was included, with a median follow-up of 14 months and a total exposure time of 55, 475 patient-months. There were 1347 peritonitis episodes with an overall peritonitis rate of 0.29 episodes per patient year. There was no significant increased risk of peritonitis with any type of pet ownership, adjusted hazard ratio (HR) of 1.09 (95% confidence interval (95% CI): 0.96–1.25). However, patients who owned both cats and dogs had an increased risk of peritonitis compared to patients without pets, HR = 1.45 (95% CI: 1.14–1.86). These results suggest that there is no increased risk of peritonitis with pet ownership except for those with both cats and dogs. This information should not prevent PD patients from owning pets but may be helpful for PD patients and their care team to direct training to minimise the risk of peritonitis.